Influencing Factor of Bore Pile Delay's Work at Green Campus to Improve Time Performance - Ariyanto, Paulus; Kussumardianadewi, Bernadette Detty (Universitas Ibn Khaldun Bogor, 2025)
The construction of the Green Campus of Sentul Defense University has suffered a setback from the planned schedule. In its planning, this project will be carried out for 5 months from May 2024 to September 2024, but it was delayed due to foundation work. The bore pile foundation work itself was carried out for 70 days from the 5th week to the 14th week. The bore pile work was planned to start in the 5th week, but in its implementation, it was only done in the 10th week, so it is necessary to identify the factors causing the delay and assess the level of importance. Therefore, this study aims to rank the factors that cause delays in bore pile work using the Relative Importance Index (RII). The variables consist of Owner (X1), Consultant (X2), Contractor (X3), Environment and K3 (X4), Materials and Equipment (X5), Construction Management (X6). The research method used is quantitative survey with descriptive analysis. The results of the analysis and calculation of the RII are the dominant factor causing the delay in bore pile work based on the variable is Owner (X1). Meanwhile, the dominant factor causing delays in bore pile work based on indicators is the Owner's delay in the approval process and making design changes (X1.2). The results of this study are expected to be a reference in the next bore pile work in the green campus project.